THEORY AND HISTORY OF ART TUITION AT SECULAR AND RELIGIOUS EDUCATION INSTITUTIONS IN THE 19TH AND EARLY 20TH CENTURIES - A. M. Kopirovsky (Russian State Vocational Pedagogical University, 2017)
Introduction. The increasing level of technicalization of life and the interest increase towards art highlight a teaching problem in modern Russia of the subjects connected with development of the heritage left by masters of last eras and works of modern writers. It is necessary to provide both new forms and methods of teaching, and judgment of the ways of conducting educational process existing earlier.The aim of the research is to identify specific features of academic subject formation patterns, in particular, the forms and stages of transitioning from random aesthetic knowledge acquisition («perception of beauty») towards more comprehensive curricula saturated with visual and factual information; and the nature of subject-specific tuition.Methodology and research methods involve the retrospective analysis of the archival materials, documents and other sources concerning the declared subject; generalization and projection of experience of the past to modern realities.Results and scientific novelty. The problems of studying of art tuition are considered at the earliest stage of teaching - in the 19th and early 20th century. Educational processes in various educational institutions as secular (Academy of Arts and universities), and religious are described (theological academies and seminaries). The materials of the first congresses of architects and artists, programs of art and pedagogical circles of the beginning of last century and the content of works of certain researchers are analysed. Basic changes in the relation to use of additional illustrative material are shown. Repeatedly expressed public requirements about familiarizing of pupils with art in voluntary to a facultative form are noted.Gradually developing orientation of educational process to teaching history of art is reflected. Poorly studied process of development of works of art within the subject «Church Archaeology» in spiritual academies and seminaries is presented and investigated. Existence of interest towards the monuments of church art in spiritual educational institutions and its earlier denied consecutive development is revealed.Practical significance. On the one hand, the contradiction between the increasing content of teaching history of art, its ambiguity, diversity is formulated; on the other hand, opportunities of perception of so complex material by pupils. The question of need of permission of this contradiction inherited by modern programs from the teaching methods existing earlier which are still used in specialized and non-special educational institutions is raised.